Adipocytokines levels at delivery, functional variation of TFAP2β, and maternal and neonatal anthropometric parameters. (29th May 2013) - Comasco, Erika; Iliadis, Stavros I.; Larsson, Anders; Olovsson, Matts; Oreland, Lars; Sundström‐Poromaa, Inger; Skalkidou, Alkistis
<x xml:space="preserve">Abstract</x> Objective Adipocytokines participate in the regulation of glucose metabolism and fetal development. The transcription factor activating protein 2B (TFAP2β) has been associated with adipocytokine regulation, and gene variations with type 2 diabetes and obesity. This study investigated associations between maternal TFAP2B variation, adipocytokine levels, and maternal and neonatal anthropometric characteristics. Design and Methods A population‐based sample of women was followed from delivery to 6 months postpartum. Adiponectin, leptin, and interleukin‐6 levels at delivery, and maternal as well as neonatal anthropometric variables were assessed. The TFAP2β intron 1 variable number tandem repeat (VNTR) was genotyped. Results Maternal interleukin‐6 correlated positively with leptin at delivery, with peripartum weight changes and weight of newborn males, adjusted for potential confounders. Leptin at delivery was associated with TFAP2β intron 1 VNTR genotype, adjusted for confounders, maternal weight and negatively with birth weight among female neonates. A path model suggested a link between TFAP2β genotype, leptin levels, and newborn females' weight. Conclusions The present results stress a role for the TFAP2 β in adiposity‐related conditions and intrauterine growth. The association between neonatal birth weight and maternal adipocytokine levels, together with the observed sex effect, call for further studies on the mechanisms behind neuroendocrine fetal programming.